Peningkatan Hasil Belajar IPA Siswa Kelas VIII SMP Parulian 1 Medan Menggunakan Model Pembelajaran Inkuiri Berbantuan Animasi - Surbakti, Mariana; Sitorus, Arjo Saputra; Sitorus, Parlindungan (Jurnal Visi Eksakta, 2021)
This research is motivated by the low science scores of students at the school, so researchers want to conduct research to find out if there is an increase in student learning outcomes in science when using the animation-assisted inquiry learning model. This type of research is quasi-experimental, the research design used is Two Group Pre test-Post test Design, eighth and the research population is all grade students of SMP Swasta Parulian 1 Medan. The instrument used in the learning outcomes test was 20 multiple choice questions which were validated by 2 science teachers in junior high school. The research result shows the score average pre test of 37.80 in 40.00 in the experimental class and control class and score post test of 82.00 in 71.00 in the experimental class and control class. Each sample group has normal data and has been tested using the Lilliefors test using SPSS, with the calculation of the results pre test obtained that L significance > 0.05, namely (0.114 > 0.05) for the experimental class and (0.148 > 0.05) for the experimental class. control, and the results post test obtained that L significance > 0.05, namely (0.066 > 0.05) for the experimental class and (0.071 > 0.05) for the control class. Furthermore, the data for both samples have homogeneous variances and have been tested using the SPSS F test, with the calculation of the results pre test obtained that F significance > 0.05 (0.728 > 0.05), and the results post test obtained that F significance 0.05 ( 0.050 ≥ 0.05). The research hypothesis test was carried out using the t-test (one-sided test). From the calculation results, it is obtained that the t significance < 0.05 is (0.000 < 0.05). then the result of hypothesis Ha is accepted. Based on the results of the overall data analysis, the t significance of < t is (0.000 < 0.05) and simple regression analysis Y = a + bx is Y = 38.347 + 0.573X. Inquiry learning model assisted by animation media can improve student learning outcomes with a large effect of increasing learning outcomes 15.5% which has a correlation coefficient of r = 0.491 (medium positive correlation). In conclusion, science learning outcomes using an inquiry learning model assisted by animation media can increase student learning outcomes by 15.5%.